Kecernaan protein dan energi metabolis akibat pemberian zat aditif cair buah naga merah (Hylocereus polyrhizus) pada burung puyuh japonica betina umur 16-50 hari - Meina Yuniarti; Fajar Wahyono; Vitus Dwi Yunianto B. I (Faculty of Animal Science, Universitas Brawijaya, 2015)
Digestibility of crude protein and energy is used to measure digestibility in poultry, digestible shows of feed substances absorbed by the body which will affect the productivity of quail. This experiment was conducted to study the effect of red dragon fruit liquid additif (Hylocereus polyrhizus), digestibility protein and metabolizable energy by quail female age 16-50 days. Experiment used 200 japanese quails females, 7 weeks age with average body weight of 13.61±0.49 g. The study was conducted in battery cages. The experiment used Completely Randomized Design with 4 treatments and 5 replications: T0 (control), T1 (Award liquid additives red dragon fruit twice a day), T2 (one a day) and T3 (two days). The dose of a liquid additive is 5 ml/quail. Observation of digestibility of crude protein (KcPK) and the energy carried by the method of total collection for 3 days, measurements using a bomb calorimeter gross energy and protein analysis using Kjeldahl method. Data were analyzed using a variety of test F at the level 5%, followed by Duncan's Multiple Range Test (UJBD) there is significant effect of the treatment each treatment was showed liquid additives red dragon fruit was not significant (P> 0.05) on crude protein digestibility and apparent metabolizable energy. The conclusion, the given of liquid additives red dragon fruit did not increase digestibility of crude protein and apparent metabolizable energy. Keywords: quail, red dragon fruit, digestibility of crude protein